Pengaruh Modal Kerja, Likuiditas, Struktur Modal dan Ukuran Perusahaan Terhadap Profitabilitas - Erica Septhasari, Lukman Surjadi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study was to obtain empirical evidence whether the independent of working capital, liquidity, capital structure and firm size affect profitability in manufacturing companies listed in Indonesian Stock Exchange during the period of 2016-2019. This study uses secondary data and processes using Software Eviews 12.0 SV. The data was obtained from the financial statements that were published by Indonesian Stock Exchange. The number of samples used 85 companies in manufacturing companies were selected using in the purposive sampling method with data count 255 during three period. This study uses descriptive statictical analysis, classic assumption test, and multiple linear regression test. The results of study show that working capital, liquidity and capital structure did not significantly influence profitability. On the other hand, company size has a significant negative affect on profitability.